Feasibility study of nanocrystalline cellulose as adsorbent of steryl glucosides from palm-based biodiesel. (July 2020) - Widdyaningsih, Liangna; Setiawan, Albert; Santoso, Shella Permatasari; Soetaredjo, Felycia Edi; Ismadji, Suryadi; Hartono, Sandy Budi; Ju, Yi-Hsu; Tran-Nguyen, Phuong Lan; Yuliana, Maria
Abstract: Increasing the content of biodiesel in the diesel fuel mixture faces some challenges due to the presence of steryl glucosides (SG) compounds, which causes the filter clogging and the reduction of engine power. In this study, coarse filter paper-based nanocrystalline cellulose (CFP-based NCC) with the crystallinity of 85.73% is selected as a potential adsorbent to separate SG compounds in palm-based biodiesel (PO–B100). The adsorption experiments were carried out at various CFP-based NCC to PO-B100 mass ratio (1:50, 1:75, 1:100, 1:125, 1:150, 1:175, 1:200) and temperature (65, 75, 85 °C). The maximum SG removal was 91.81%, obtained at 75 °C for CFP-based NCC to PO-B100 mass ratio of 1:50. The adsorption treatment also improves the cold stability of PO-B100 by reducing the cloud point from 13.2 °C to 11.5 °C. Langmuir isotherm model is best-fitted to the equilibrium adsorption data and thermodynamic studies suggested that the adsorption of SG onto the CFP-based NCC surface is spontaneous and endothermic. The isotherm and thermodynamic study showed that the mechanism governing the adsorption process may be driven by both dipole-dipole interactions and ion exchange. The adsorption results showed that CFP-based NCC has great affinity and selectivity to SG and can be considered as a promising adsorbent of SG. Highlights: CFP-based NCC has been successfully applied to remove 91.81% SG from PO-B100. Highest SG removal rate obtained at 75 °C and NCC to PO-B100 mass ratio 1:50. The cloud point of PO-B100 is reduced from 13.2 °C to 11.5 °C after adsorption. The adsorption mechanism may be driven by dipole-dipole coupling and ion exchange. CFP-based NCC has been found to have a great affinity and selectivity to SG.